Nondegree Education in Europe: Opportunities for Lifelong Learning - Gaebel, Michael; Zhang, Thérèse (International Higher Education, 2025)
<h3 id="european-higher-education-institutions-and-policy-makers-have-granted-increasing-attention-to-the-importance-of-shorter-nondegree-education-provision-as-avenues-to-offer-upskilling-and-reskilling-to-learners-and-workers-but-also-as-a-contribution-of-higher-education-to-lifelong-learning-in-society-more-generally-a-recent-study-from-the-european-university-association-provides-an-overview-of-the-extent-to-which-such-shorter-learning-provision-is-present-in-the-european-higher-education-area-this-paper-also-points-to-challenges-identified-by-higher-education-institutions-themselves-and-ways-forward-in-a-context-where-processes-and-regulations-are-geared-by-default-toward-degree-education-but-where-complementarity-between-longer-and-shorter-education-provision-might-become-key-to-the-future-of-learning-in-higher-education" data-pm-slice="1 1 []">European higher education institutions and policy makers have granted increasing attention to the importance of shorter, nondegree education provision, as avenues to offer upskilling and reskilling to learners and workers, but also as a contribution of higher education to lifelong learning in society more generally. A recent study from the European University Association provides an overview of the extent to which such shorter learning provision is present in the European Higher Education Area. This paper also points to challenges identified by higher education institutions themselves and ways forward, in a context where processes and regulations are geared by default toward degree education, but where complementarity between longer and shorter education provision might become key to the future of learning in higher education.